Real-Time Monitoring System of Landslide Based on LoRa Architecture - Wang, Chenhui; Guo, Wei; Yang, Kai; Wang, Xi; Meng, Qingjia (Frontiers in Earth Science, 2022)
The equal time interval sampling in the existing landslide monitoring system cannot detect the abnormal change of landslides in real time. This study proposes a novel landslide monitoring method based on the long range (LoRa) network and intelligent sensing Internet of Things (IoT) to address these drawbacks. The overall structure, hardware circuit, and software design of intelligent sensing monitoring technology are described comprehensively. The designed adaptive data collection strategy can effectively capture abnormal changes in the landslide monitoring parameters, which provides a better alternative monitoring scheme for the real-time data collection of disaster body status. Furthermore, it can ensure data accuracy for the research of intelligent large-scale landslide disaster monitoring and prediction. The field test demonstrates that the proposed system presents the technical characteristics of low power consumption, self-organizing network, stable and reliable communication, and long transmission distance, which is effective for mountain landslide monitoring in harsh environments.